Analisis Minat Belajar Mahasiswa Pendidikan Bahasa Dan Sastra Indonesia Universitas Riau Pada Mata Kuliah Arab Melayu Kelas 2021 B - Zelpi Ayuni; Delma Lestari; Elvira Oktarianti; Hasnah Faizah (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Education is "a conscious and planned effort to create an atmosphere of learning and learning so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble morals and skills needed by themselves and society Students' interests will affect their learning outcomes as well. Interest is a sense of preference and interest caused by a source of motivation that drives a person. The method used in this research is quantitative method. The sampling technique was carried out by probability sampling. Survey research is a type of sample data research collected through questionnaires or interviews to explain various aspects of the population. In survey research, researchers select a sample of participants through questionnaires. Data analysis was carried out to determine the percentage of interest of Indonesian Language and Literature Education 2021 B students in Malay Arabic courses. Based on the frequency distribution and percentage of learning interest, one respondent obtained the highest score of 100 with a percentage of 5% of the entire sample. one respondent (5% of the sample) obtained the lowest score of 70 categorized as very lacking in learning interest. scores 75 and 80 were obtained by seven respondents from each of the series percentage values, namely 20% for scores 85 with 90 and 25% for scores 95